Jaminan Dan Agunan Dalam Pembiayaan Bank Syariah Dan Kredit Bank Konvensional - Fitriani, Ifa Latifa (UI Scholars Hub, 2017)
If we look into the collateral and additional collateral concept in conventional banking and Islamic banking, it has different fundamental background and principle. Collateral in conventional banking system appears due to the position and condition of the creditor-debitor relationship. The relationship has implicedto present the legal obligation of collateral things according to Article 1131 Book of Civil Law in every credit transaction. Islamic banking system has taken the consept of collateral from Rahn and kafalah, eventhough the reality shows the practice of collateral and additional collateral still using legal collateral norm of Indonesia’s positive law sistem that based on Westren law